2021
DOI: 10.1186/s13071-021-04844-w
|View full text |Cite
|
Sign up to set email alerts
|

A conserved female-specific larval requirement for MtnB function facilitates sex separation in multiple species of disease vector mosquitoes

Abstract: Background Clusters of sex-specific loci are predicted to shape the boundaries of the M/m sex-determination locus of the dengue vector mosquito Aedes aegypti, but the identities of these genes are not known. Identification and characterization of these loci could promote a better understanding of mosquito sex chromosome evolution and lead to the elucidation of new strategies for male mosquito sex separation, a requirement for several emerging mosquito population control strategies that are depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 56 publications
5
19
0
Order By: Relevance
“…The dosage of Rbfox1.457 correlated directly with the percentage of larval mortality (Figure 1f), with the LD 50 determined to be 28 mg. Larvicide activity was also verified in semi-field trials conducted at an outdoor rooftop laboratory in Notre Dame, IN, where 93 ± 1% larval mortality was observed following Rbfox1.457 treatment (Figure 1d; p < 0.001 vs. control). These studies, combined with previous studies in which yeast IRP larvicides were shown to function in different types of water [10,11] and in an assortment of different sized containers with varied water volumes and larval densities [6,10,11,32,33] provide further evidence that yeast IRPs may represent a new larvicidal intervention, adding Rbfox1.457 to the growing arsenal of yeast larvicides.…”
Section: Development Of An Rnai-based Yeast Pesticide That Can Be Deployed As An Atsbmentioning
confidence: 56%
“…The dosage of Rbfox1.457 correlated directly with the percentage of larval mortality (Figure 1f), with the LD 50 determined to be 28 mg. Larvicide activity was also verified in semi-field trials conducted at an outdoor rooftop laboratory in Notre Dame, IN, where 93 ± 1% larval mortality was observed following Rbfox1.457 treatment (Figure 1d; p < 0.001 vs. control). These studies, combined with previous studies in which yeast IRP larvicides were shown to function in different types of water [10,11] and in an assortment of different sized containers with varied water volumes and larval densities [6,10,11,32,33] provide further evidence that yeast IRPs may represent a new larvicidal intervention, adding Rbfox1.457 to the growing arsenal of yeast larvicides.…”
Section: Development Of An Rnai-based Yeast Pesticide That Can Be Deployed As An Atsbmentioning
confidence: 56%
“…Promising strategies of female killing have been pursued based on larval consumption of the yeast Saccharomyces cerevisiae engineered to deliver interfering RNA to specifically kill females. RNAi-mediated silencing of gamma-glutamyl transpeptidase (GGT), methylthioribulose 1-phosphate dehydratase (MtnB), and lncRNA genes resulted in significant female death and no impact on male survival or fitness [55][56][57]. This system is advantageous as heat-killed yeast retains its ability to induce effective gene silencing, making packaging, shipping, and storage of this diet straightforward and extremely cost-effective.…”
Section: Methods To Selectively Eliminate or Incapacitate Femalesmentioning
confidence: 99%
“…This differentiation was detected as a difference in the read depth of coverage (Matthews et al 2018) and the frequency of SNPs between males and females (Fontaine et al 2017). Additionally, several studies have reported sex-specific lethality when genes in the vicinity of the M-locus were recombined or silenced via RNAi (Krzywinska et al 2016; Wood 1990; Mysore et al 2021b). Moreover, an unexpected mechanism of inheritance bias in males was recently detected for a gene closely-linked to the M-locus that was targeted by a gene drive element (Verkuijl et al 2022).…”
Section: Introductionmentioning
confidence: 99%